Behavioral phenotyping of mice lacking the K ATP channel subunit Kir6.2. - Deacon, R; Brook, R; Meyer, D; Haeckel, O; Ashcroft, F; Miki, T; Seino, S; Liss, B (2006)
ATP-sensitive potassium (K(ATP)) channels are expressed in various tissues and cell-types where they act as so-called metabolic sensors that couple metabolic state to cellular excitability. The pore of most K(ATP) channel types is built by Kir6.2 subunits. Analysis of a general Kir6.2 knockout (KO) mouse has identified a variety of different functional roles for central and peripheral K(ATP) channels in situations of metabolic demand. However, the widespread distribution of these channels suggests that they might influence cellular physiology and animal behavior under metabolic control conditions. As a comprehensive behavioral description of Kir6.2 KO mice under physiological control conditions has not yet been carried out, we subjected Kir6.2 KO and corresponding wild-type (WT) mice to a test battery to assess emotional behavior, motor activity and coordination, species-typical behaviors and cognition. The results indicated that in these test situations Kir6.2 KO mice were less active, had impaired motor coordination, and appeared to differ from controls in their emotional reactivity. Differences between KO and WT mice were generally attenuated in test situations that resembled the home cage environment. Moreover, in their home cages KO mice were more active than WT mice. Thus, our results suggest that loss of Kir6.2-containing K(ATP) channels does affect animal behavior under metabolic control conditions, especially in novel situations. These findings assign novel functional roles to K(ATP) channels beyond those previously described. However, according to the widespread expression of K(ATP) channels, these effects are complex, being dependent on details of test apparatus, procedure and prior experience.